MENDENGARKAN GRAPEVINE COMMUNICATION: STUDI TENTANG PENYEBARAN INFORMASI INFORMAL DAN DAMPAKNYA TERHADAP KESEHATAN MENTAL - Nursanti, Siti; Nurhanan, Hanna (Jurnal Ilmu Komunikasi, 2024)
This research aims to explore the dynamics of information dissemination through grapevine communication—an informal communication channel—and its impact on individuals' mental health in the workplace. Using a qualitative approach with participant observation methods, the researcher directly engaged in participants' daily lives to naturally observe how unofficial information is spread and received, as well as how the process affects psychological conditions. The findings indicate that grapevine communication can be a source of emotional tension, uncertainty, and insecurity, especially when circulating information is ambiguous or has the potential for conflict. These findings emphasize the importance of strengthening interpersonal communication literacy and adopting empathy-based communication management to safeguard mental health amid the uncontrolled flow of informal information.